Pengaruh Environmental Cost dan Environmental Performance terhadap Environmental Disclosure pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Abimanyu Abimanyu; Yuztitya Asmaranti (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study investigates the effect of environmental costs on the level of environmental information transparency in manufacturing companies in the basic materials subsector, while providing empirical evidence regarding the relationship. Environmental costs are calculated through the ratio of corporate social responsibility (CSR) burden to the organization's net profit. Meanwhile, the company's environmental performance is evaluated using the PROPER rating on an ordinal scale. The level of environmental coverage is measured comprehensively through the Clarkson index which covers various dimensions of existing reporting. A quantitative approach with multiple linear regression analysis is applied to test the relationship between variables. In selecting the sample, a purposive sampling technique was used by considering the completeness of the data and certain sector criteria, resulting in 35 companies as the final sample that met the analysis requirements. The results of the study revealed that an increase in environmental costs is directly proportional to a significant increase in environmental coverage. This indicates that company investment in environmental programs encourages more transparent reporting practices. In addition, environmental performance as reflected in the PROPER rating is also proven to have a positive and significant effect on the extent of environmental coverage.